Justifying Particular Reasoning in a Legal Context: On Neil MacCormick's ‘Universalisable Particular Thesis’ - Wu, Jingjing (Informal Logic, 2020)
Particular reasoning is arguably the most common type of legal reasoning. Neil MacCormick proposed that, in a legal context, justifiable particular reasoning has to be universalizable. This paper aims to: (1) investigate MacCormick’s thesis; (2) explain how a particular can ever be universal by drawing inspiration from Scott Brewer’s formula on reasoning by analogy; (3) further comprehend MacCormick’s thesis by considering some of the arguments advanced by its opponents; (4) use the ‘pilot-judgement procedure’ developed by the European Court of Human Rights as an example to illustrate the relevance of the universalizable particular thesis in today’s legal practices.